Business Development Strategy For Sale Pisang Mak Mixsyen In Suka Jaya Village, South Bengkulu - Rahmadania, Emilda; Kresnawati , Kresnawati; Yanti , Rina Trisna (Universitas Dehasen Bengkulu, 2026)
Micro, small and medium enterprises (MSMEs) contribute more than 61% to the national Gross Domestic Product (GDP) and employ more than 97% of the workforce in Indonesia. The MSME sector has a high adaptability, especially in commodity-based businesses that utilise the potential of local natural resources. The purpose of this study is to determine strategies that encourage the development of the Sale Pisang Mak Mixsyen business in Suka Jaya Village, South Bengkulu, and to formulate appropriate development strategies through SWOT analysis and the determination of strategic priorities using the Analytical Hierarchy Process (AHP) method. This research method uses a descriptive qualitative-quantitative research type. This research was conducted at the Sale Pisang Mak Miksen MSME. The data collection techniques were interviews and SWOT questionnaires. The data analysis techniques used in this study were SWOT matrix calculations and strategy weighting using the Analytical Hierarchy Process (AHP). The results of the study showed that the factors in the development of the ‘Mak Mixsyen’ banana sale business were that the product had a distinctive taste and was durable (strength) with a score of 1.74, limited capital, few product variants, and unstructured business management (weaknesses) with a score of 1.05, the use of digital technology and government support for MSMEs (opportunities) with a score of 1.92, and unstable raw material prices (threats) with a score of 0.64. Based on the SWOT analysis results, the appropriate strategic alternative for developing the ‘Mak Mixsyen’ banana sale business is in Quadrant I with coordinates 0.68:1.28, namely the S-O strategic alternative, which includes improving quality and adding variants, utilising social media for promotion, and utilising government support for MSMEs. The AHP results prioritise the strategic alternatives for developing the ‘Mak Mixsyen’ banana sale business as improving quality and adding variants, utilising social media for promotion, and utilising government support for MSMEs, as well as improving business management